(3GdSMQ GdeHjf haJhQ CdMGX GdYjf ajeG SfM ef CNHGQ Gdjef hCgdjg GdejGejf ef SfI EKfjf hJSYjf HYO GdCda Edi haGA GdNeSjf HYO EMOi YTQI ef dejfs - (3MSGe GdOjf MSf Hf GdMSf , Hf GdbGSe Hf ZGdHs
(3ChdgG (B:s
(3CeG HYO ,abO SCdfi UMH hYhdhG RHCf CLeY ddjef ef GdMhGOK GdcGFfI HYO GdJSYjf hCda Edi fja hNeSjf ef GdSfjf s
(3BNQgG (B:s
(3hEdi YGe GdKdGKjf GfJgi GdLRA GdChd ef GdSMQ GdeHjf , hjJdhg GdLRA GdKGfi Edi haGA GdNeSjf , hgh GdeSei HhTi UfYG s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B285s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B552 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B228 - (3U (B405 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs